Perceptions of adults with overweight/obesity and chronic musculoskeletal pain: An interpretative phenomenological analysis. Issue 5 (24th January 2018) - Cooper, Lesley; Ells, Louisa; Ryan, Cormac; Martin, Denis
Abstract : Aims and objectives: To gain insight into the lived experience of adults with overweight/obesity and chronic musculoskeletal pain. Knowledge gained will inform healthcare professionals about the complexity of the weight–pain relationship and enable more effective engagement with this population. Background: Quantitative studies show links between weight and pain. Adults with overweight/obesity are more likely to experience comorbidity; however, qualitative research describing the complexities of the relationship is limited. Methods: A purposive sample of adults with overweight/obesity and chronic musculoskeletal pain participated in face‐to‐face interviews. Interviews were audio‐recorded, transcribed verbatim and analysed using interpretive phenomenological analysis. Results: Eighteen adults (16 female) aged 29–71, body mass index ≥25–46, participated in this study. Three superordinate themes emerged: "pain as a motivator and barrier to weight loss"; "fear of weight causing more damage"; and "activity is positive." Pain motivates some individuals to lose weight while simultaneously inhibiting weight loss efforts. Participants' perception that extra pressure caused by their weight further damaged joints contributed to fear and catastrophising. Fear is often exacerbated by healthcare professionals' descriptions of musculoskeletal damage, or participants' perception of healthcare professionals' attitude towards people with overweight/obesity. Conversely, individuals acknowledged the benefits of increased activity. Conclusion: Adults with overweight/obesity and chronic musculoskeletal pain in this study identified a bidirectional relationship between their weight and pain that challenged their weight loss efforts. Overweight/obesity contributed to fear and catastrophising, which resulted in avoidance of exercise that would have assisted their weight loss. Relevance to clinical practice: Healthcare professionals need to understand the complex relationship between weight and pain, and their patients' understanding of that relationship. Healthcare professionals should use therapeutic communication to reduce the fear of weight causing damage, and thus promote physical activities that will contribute to weight loss. It is also important to ensure that the language used with this patient group does not stigmatise individuals, or cause or exacerbate fear of normal movement.